PENGARUH HARGA DAN CITRA MEREK TERHADAP KEPUTUSAN PEMBELIAN TIKET MASKAPAI CITILINK OLEH WISATAWAN NUSANTARA DI BANDARA NGURAH RAI, BALI - I Gede Cahaya Adi Putra; I GPB Sasrawan Mananda; Ni Gusti Ayu Susrami Dewi (Department of Tour and Travel Studies, Faculty of Tourism, Udayana University, 2016)
Citilink airlines is one of LCC ( Low Cost Carrier ) flight in Indonesia, under management of Garuda Indonesia and established in 2001. The purpose of this research is to find out the influence of prices and brand images partial and simultaneous with domestic tourits decision to purchase the ticket and the location of this research at Ngurah Rai Airport, Bali. The sample technique used is purposive sampling and techniques of the collected sample were used with accidental sampling. The number of respondents used in this research are 150 of respondents. Analysis data used was validity test, reliability, assumption classical test, multiple regression analysis, analysis of koefisien determination, and Likert scale The results of research is that the price of ( x1 ) has positive effects and significant of decision of ( y ) as Citilink ticket, with a significance value af 0,000 which is less than ? = 0.05 and tcount of 4,805 is larger than ttable 1,655. Brand images variables ( x2 ) has some positive effects and significant of the decision of the purchase of ( y ) Citilink ticket, with a significance value at 0,000 which is less than ? = 0.05 and tcount of 6,750 is larger than ttable 1,655. Variable of prices ( x1 ) and brand images ( x2 ) has some positive effects and significant of the decision of the purchase of ( y ) Citilink ticket, with a significance value 0,000 which is less than ? = 0.05 and fcount of 115,605 larger than ftable 3,06.